2004
DOI: 10.1300/j076v39n03_04
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Connecticut's In-Prison Substance Abuse Treatment

Abstract: Over the past two decades, the criminal justice population in the US has grown by over 200%, most of this due to an increase in drug-involved offenders. Although there is good evidence that prison-based substance abuse treatment programs can be effective in reducing rearrest, few cost-effectiveness studies have been conducted. Using data from the Connecticut Department of Correction and the Connecticut Department of Mental Health and Addiction Services (DMHAS), we compared the cost-effectiveness of four tiers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…One dollar spent on drug courts is estimated to save approximately $4 in avoided costs of incarceration and health care,38 and prison-based treatment saves between $2 to $6 39. These economic benefits in part reflect reductions in criminal behavior 40,41…”
Section: Drug Abuse Treatment Effectiveness In the Criminal Justice Smentioning
confidence: 99%
“…One dollar spent on drug courts is estimated to save approximately $4 in avoided costs of incarceration and health care,38 and prison-based treatment saves between $2 to $6 39. These economic benefits in part reflect reductions in criminal behavior 40,41…”
Section: Drug Abuse Treatment Effectiveness In the Criminal Justice Smentioning
confidence: 99%
“…They found that inprison treatment results in a cost of $45 to $65 per incarceration day avoided and is more cost-effective if combined with aftercare. Daley et al (2004) examine the costs and benefits of voluntary prison treatment programs operated by the Connecticut Department of Correction with a sample of inmates released from prison between 1996 and 1997. They find a significant reduction in rearrest for subjects in the treatment group during the 1-year period following release compared with subjects in the untreated comparison group.…”
Section: Economic Analyses Of Offender Treatment Programsmentioning
confidence: 99%
“…The main exceptions are evaluations of health care interventions delivered within criminal justice settings, such as services for mental health and substance misuse problems. 54 Cost-offset methods have been used but these often take a limited cost and outcome perspective, as do the small number of cost-benefit analyses that exist. 55,56 Attention has tended to focus on the taxpayer perspective, which limits the evaluation to the question of whether a publicly funded intervention pays for itself (i.e.…”
Section: The Role Of Economic Evidence In Crime and Justicementioning
confidence: 99%